RURAL HERITAGE IN THE AUSTRIAN RURAL DEVELOPMENT PROGRAMME - Wagner, Klaus (Economics of Agriculture, 2011)
This paper deals with the results of the mid-term review of the Austrian Rural Development Programme 2007-2013 as part of the European Unions Common Agricultural Policy. The measure to conserve and improve rural heritage covers the felds Nature Conservation and Environmental Protection, National Parks, Cultural (Man-Made) Landscape, Forestry, Water and the Development Potential of the Alpine Region. Although the measures were very much appreciated, they met with very differing responses and implementation efforts, depending on the region. There seem to be startup delay problems with new measures and high coordination needs where cross-sector measures are concerned. In addition, people seem to be having problems displaying the actions actual impact with the indicator set provided by the EU. Frequently, the outcome can only be determined in the long run and in combination with a whole string of other factors.